Inhibition of growth of the transplantable rat chondrosarcoma by analogs of hypothalamic hormones - Redding, T. W. (1983)
The Swarm chondrosarcoma is a hormone-responsive tumor whose growth is dependent on growth hormone, somatomedins, and glucocorticoids. Our previous work showed that partial functional hypophysectomy can be achieved by chronic administration of the luteinizing hormone-releasing hormone (LH-RH) analog [D-Trp(6)]LH-RH, which lowers blood levels of LH and follicle-stimulating hormone. We have also demonstrated that somatostatin (SS)-28 or analogs of SS-14 depress serum prolactin, growth hormone, and corticotropin (ACTH) levels. Consequently, we investigated the effect of subcutaneous injection of these analogs on the growth of Swarm chondrosarcoma 3 days after transplanting it into male Sprague-Dawley rats. At autopsy, tumor volume was measured and tumors and various organs were weighed. In rats treated with three different analogs of SS-14, [p-NH(2)-Phe(4)]SS, [D-5-F-Trp(8)]SS, and [D-5-MeO-Trp(8)]SS, in doses of 30 μg once or twice daily for 14-30 days, there was a significant reduction in tumor volume and/or weight as compared with control rats. The longer acting SS-28 or its analog Val-Gly-Tyr-Val-Ile-Leu-Gly-SS-28, given in doses of 30 μg/day for 22-30 days, also significantly decreased tumor weight and/or volume. In three experiments, [D-Trp(6)]LH-RH (30-60 μg/day), administered alone or together with analogs of SS-14, decreased tumor weight and/or volume. Serum growth hormone and prolactin levels in rats bearing the tumors were significantly decreased after treatment with [D-5-F-Trp(8)]SS or with [D-Trp(6)]LH-RH. The inhibition of growth of the Swarm chondrosarcoma in rats by these analogs suggests that they might lead to a new endocrine therapy for chondrosarcomas, osteosarcomas, and related hormone-dependent neoplasias.